2011
DOI: 10.2165/11585880-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Exenatide Extended-Release After Single and Multiple Dosing

Abstract: These studies demonstrated that (i) a single subcutaneous dose of exenatide ER resulted in dose-related increases in plasma exenatide concentrations; (ii) single-dose exposure successfully predicted the weekly-dosing exposure, with 0.8 mg and 2 mg weekly subcutaneous doses of exenatide ER eliciting therapeutic concentrations of exenatide; and (iii) weekly dosing with either 0.8 or 2 mg of exenatide ER improved fasting plasma glucose control, whereas only the 2 mg dose was associated with improved postprandial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
136
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 21 publications
13
136
0
Order By: Relevance
“…Weekly exenatide administration led to clinically significant improvements in glycaemic control that were evident by week 4, and steady‐state concentration of exenatide at approximately week 8 was consistent with previous studies 16, 17, 18, 19. Continuous exposure of exenatide translated into similar glucose‐lowering effects at the beginning and end of the week.…”
Section: Discussionsupporting
confidence: 87%
“…Weekly exenatide administration led to clinically significant improvements in glycaemic control that were evident by week 4, and steady‐state concentration of exenatide at approximately week 8 was consistent with previous studies 16, 17, 18, 19. Continuous exposure of exenatide translated into similar glucose‐lowering effects at the beginning and end of the week.…”
Section: Discussionsupporting
confidence: 87%
“…36). As expected, blood glucose levels were reduced by Ex-4 within 24 hours and remained lower during the subsequent treatment period ( Figure 2C and Supplemental Figure 2E).…”
Section: Introductionsupporting
confidence: 80%
“…10, 31-35). The circulating Ex-4 level in our system (~4 ng/ml) was much higher than the basal plasma GLP-1 level in mice (48,49) or healthy humans (50) but close to the therapeutic concentration target for GLP-1R agonists in clinical use (36). The duration of Ex-4 infusion in our study was shorter (28 days) Table 1 for the quantification of TUNEL + β cells in PBS+saline-treated, Ex-4+saline-treated, PBS+FK506-treated, and Ex-4+FK506-treated graft samples from 3 juvenile donors.…”
Section: Discussionmentioning
confidence: 65%
“…S1, A and B, respectively; Supplemental Material for this article can be found on the AJPEndocrinology and Metabolism web site). The mean exenatide plasma concentration at the termination of this study was 166 Ϯ 24 pg/ml and was in the range of concentrations found in patients dosed with exenatide (20,25). Additionally, 7.2 nmol·kg Ϫ1 ·day Ϫ1 of exenatide significantly decreased Hb A 1c , plasma glucose, and body weight in HF-STZ mice compared Acute effects of exenatide on amylase and lipase during chemically induced pancreatitis in normal or diabetic rats or diabetic mice.…”
Section: Effect Of Single-dose or Subchronic Administration Of Exenatmentioning
confidence: 54%
“…Cytokine concentrations were calculated using the four-parameter logistic standard curve fit method (SoftMax Pro; Molecular Devices, Sunnyvale, CA). Plasma exenatide concentrations were measured using an immunoenzymetric assay developed at Amylin Pharmaceuticals, as described previously (20).…”
Section: Methodsmentioning
confidence: 99%